Knowledge, practice and awareness of adolescent girls on human papillomavirus vaccine - Akhter, Nusur; Nasrin, Sonia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Human papillomavirus (HPV) is a significant public health concern, particularly among adolescents, as it is a leading cause of cervical cancer and other HPV-related diseases. Despite the availability of an effective vaccine, knowledge and awareness about HPV and its prevention remain limited, especially among young girls. This study aims to assess the knowledge, practice, and awareness of adolescent girls regarding the HPV vaccine. Methods: The study was conducted at department of obstetrics and gynaecology, Anwer Khan modern medical college and hospital, Dhaka, Bangladesh from July, 2023 to June, 2024. A cross-sectional descriptive study design was employed, targeting adolescent girls aged 13 to 19 years. The study population consisted of students from five secondary schools within the urban and peri-urban areas of the district. A total of 300 participants were included in the study. Results: The study of 300 participants reveals that the majority are aged 15-16 years (40%), followed by 17-18 years (30%). Most participants are in senior secondary (1-2) (50%), and 60% are aware of HPV, with school programs being the most common source of awareness. Knowledge of HPV transmission and the HPV vaccine is limited, with 40% having correct knowledge about transmission and 30% possessing adequate vaccine knowledge. Vaccination rates are low, with only 40% vaccinated, primarily due to a lack of awareness. Most participants recommend increasing awareness campaigns (50%) and reducing vaccine costs (25%). Conclusions: This study concludes that a majority (60%) of the participants were aware of HPV, only 40% demonstrated correct knowledge of its transmission, and an even smaller proportion (30%) had adequate knowledge about the HPV vaccine itself. The low vaccination rate of 40% reflects the challenges in increasing uptake, with the primary barrier being a lack of awareness.